2022
DOI: 10.1093/ptj/pzab258
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mat Pilates Training Combined With Aerobic Exercise Versus Mat Pilates Training Alone on Blood Pressure in Women With Hypertension: A Randomized Controlled Trial

Abstract: Objective The purpose of this study was to determine the effects of mat Pilates (MP) versus MP plus aerobic exercise (AE) compared with the effects of no intervention on ambulatory blood pressure (BP) in women with hypertension. Methods This 3-arm, parallel-group randomized clinical trial assessed 60 women who had hypertension and were 30 to 59 years old. The intervention lasted 16 weeks, and the participants were allocated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…This secondary analysis was embedded within a controlled, single-blind, randomized controlled trial (RCT) aiming to verify the long-term effects of MP and MP supplemented with AE training on ambulatory BP in hypertensive women [ 14 ]. Therefore, most of the methodology used in this secondary analysis was the same as for the RCT [ 14 ]. The study was carried out for 16 weeks at the School Clinic of the Catholic University of Brasília, conducted according to the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This secondary analysis was embedded within a controlled, single-blind, randomized controlled trial (RCT) aiming to verify the long-term effects of MP and MP supplemented with AE training on ambulatory BP in hypertensive women [ 14 ]. Therefore, most of the methodology used in this secondary analysis was the same as for the RCT [ 14 ]. The study was carried out for 16 weeks at the School Clinic of the Catholic University of Brasília, conducted according to the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…The study is reported according to the Consolidated Standards of Reporting Trials Statement for Randomized Trials of Nonpharmacologic Treatments and the Template for Intervention Description and Replication [ 19 , 20 ]. The details of the RCT have been reported previously [ 14 ], jointly with randomization, allocation concealment, and blinding [ 14 ]. In brief, the participants were randomized into three groups: MP: performed traditional MP exercises, MP+AE: performed traditional MP exercises with additional bouts of AE, and CG: the participants did not perform physical training during the experimental period.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations